D-optimal design optimization of jatropha curcas L. seed oil hydrolysis via alkali-catalyzed reactions - Jumat Salimon,; Bashar Mudhaffar Abdullah,; Nadia Salih, (Universiti Kebangsaan Malaysia, 2012)
Potassium hydroxide (KOH)-catalyzed reactions were utilized to hydrolyze Jatropha curcas seed oil. In this study, the effect of ethanolic KOH concentration, reaction temperature and reaction time to the free fatty acid (FFA) produced were investigated. D-Optimal Design was employed to study the significance of these factors and optimum conditions for the technique was predicted. The results showed that ethanolic KOH concentration was a significant variable for hydrolysis of J. curcas seed oil. In 18 experimental designs, FFA percentage of hydrolyzed J. curcas seed oil increased from 1.89% to 102.2%. The optimal conditions of response were found at 1.75M of ethanolic KOH, 65 °C and at 2 h reaction time. Fourier Transforms Infrared Spectroscopy (FTIR) spectrum analysis confirmed the concentration of ethanolic KOH i.e. at 1.00, 1.50 dan 1.75 M affect the percentage yields of J. curcas seed oil hydrolysis process.